Recent activation of the plaque immune response in coronary lesions underlying acute coronary syndromes - van der Wal, A C; Piek, J J; de Boer, O J; Koch, K T; Teeling, P; van der Loos, C M; Becker, A E (Heart (British Cardiac Society), 1998)
Objective To discriminate between chronic inflammation and acute activation of the plaque immune response in culprit lesions of patients with acute coronary syndromes. Design Retrospective study. Setting Tertiary referral centre. Subjects 71 patients having coronary atherectomy were classified according to their ischaemic syndrome: stable angina (n = 23); stabilised unstable angina (n = 18); refractory unstable angina (n = 11); and acute myocardial infarction (n = 19). Main outcome measures Immunohistochemical measurement of interleukin 2 receptor (IL-2R) (CD25) positive cells expressed as a percentage of the total amount of (CD3 positive) T lymphocytes in frozen sections of atherectomy specimens. Results The number of lesions containing IL-2R (CD25) positive T cells increased with severity of the ischaemic coronary syndrome (stable angina, 52%; stabilised unstable angina, 77.8%; refractory unstable angina, 90.9%; acute myocardial infarction, 89.4%). The percentage of activated T cells (CD25/CD3 ratios ×100) increased in lesions associated with refractory unstable angina (7.8%) and acute myocardial infarction (18.5%), compared with those in lesions associated with either chronic stable angina (2.2%) or stabilised unstable angina (3.3%). Conclusions An increase in the percentage of IL-2R positive T lymphocytes in culprit lesions of patients with acute coronary syndromes indicates recent activation and amplification of the immune response within plaques. This may result in a burst of inflammatory products with tissue degrading and vasoactive properties and, hence, could initiate or accelerate the onset of an acute coronary event.